Impact of entrepreneurial training on performance of small and medium enterprises in Union Territory of J&K: A case study of Rajouri district - Ahmad Bhat , Muzzafar (International Journal of Psychosocial Rehabilitation, 2019)
Small and medium enterprises have been a focal point of government of India to cater the needs of unemployment in the country. Since it is not possible for the government to provide jobs to ever one. Hence to address the menace of unemployment in the country, it is imperative to provide a healthy environment to the small and medium enterprises sector. The said sector has become a driving engine of the economy of the country in recent years. To promote the sector govt. has initiated various training programmes which are aimed at developing the sector. The present study has been carried out with the same purpose to assess the impact of various training programmes on the performance of the small and medium enterprises in Rajouri district of Jammu division.